Nova cluniacensia : les feuillets de garde du manuscrit Paris BnF nal 1236 et la création de la liturgie clunisienne - Eduardo Henrik Aubert (Bulletin du Centre d’Études Médiévales d’Auxerre)
This article consists of an in-depth examination of three folios originating from a notated monastic antiphoner, currently employed as flyleaves in manuscript Paris, BnF, nal 1236. Based on a multi-faceted – codicological, palaeographical, liturgical and musical – approach, we substantiate the claim that they were written in Cluny around the year 1000. They are thus the remains of the oldest known chant book whose writing can be ascribed to the famous Burgundian abbey. By resorting to comparative methods, this source is contextualised with reference to an array of other sources variously related to Cluny, extending from those that were also written in Cluny to rather distant ones. This method allows one to collect the traces of a history going back to the very origins of Cluniac liturgy to its diffusion in the reforming movements of the tenth to twelfth centuries, including a period of major creativity that must have taken place in the abbey itself.